Cryo-EM structure of human type-3 inositol triphosphate receptor reveals the presence of a self-binding peptide that acts as an antagonist - Azumaya, Caleigh M.; Linton, Emily A.; Risener, Caitlin J.; Nakagawa, Terunaga; Karakas, Erkan (The Journal of biological chemistry, 2020)
Calcium-mediated signaling through inositol 1,4,5-triphosphate receptors (IP3Rs) is essential for the regulation of numerous physiological processes, including fertilization, muscle contraction, apoptosis, secretion, and synaptic plasticity. Deregulation of IP3Rs leads to pathological calcium signaling and is implicated in many common diseases, including cancer and neurodegenerative, autoimmune, and metabolic diseases. Revealing the mechanism of activation and inhibition of this ion channel will be critical to an improved understanding of the biological processes that are controlled by IP3Rs. Here, we report structural findings of the human type-3 IP3R (IP3R-3) obtained by cryo-EM (at an overall resolution of 3.8 Å), revealing an unanticipated regulatory mechanism where a loop distantly located in the primary sequence occupies the IP3-binding site and competitively inhibits IP3 binding. We propose that this inhibitory mechanism must differ qualitatively among IP3R subtypes because of their diverse loop sequences, potentially serving as a key molecular determinant of subtype-specific calcium signaling in IP3Rs. In summary, our structural characterization of human IP3R-3 provides critical insights into the mechanistic function of IP3Rs and into subtype-specific regulation of these important calcium-regulatory channels.